Implementasi Pelatihan Seni Banjari sebagai Upaya Peningkatan Kreativitas dan Religiusitas Pemuda di Desa Sahang, Kecamatan Ngebel, Kabupaten Ponorogo - Nyono Sugiarto; Lisma Meilia Wijayanti (Social Science Academic, 2025)
Banjari art training is one of the strategic efforts to enhance the creativity and religiosity of youth, particularly in rural areas. Sahang Village, as a region with significant potential in religious art and culture, has utilized this training activity as a medium for youth self-development to become more productive, creative, and spiritually sensitive. The implementation method was carried out through a participatory approach, involving youth organizations such as Karang Taruna and mosque youth groups. The results show an increase in youth interest in Islamic art, stronger social bonds, and the creation of a positive space for expression that helps reduce deviant behavior. Banjari art has proven to be effective as a medium for religious development as well as a means of preserving Islamic culture in modern society.